Síntese de nanomagnetos moleculares contendo ligantes de terminação e oxamatos - Wdeson Pereira Barros (2009)
In this work, were described some procedures to obtain systems of molecular nanomagnets with controlled dimensionality through a previously designed approach. Compounds such as Cu(opba)]2- and trinuclear [Cu{Cu(opba-dN)}2]2- were used to form the central blocks, with opba standing for o-phenylenebis(oxamato). To controlthe overall structure dimension, compounds containing the end-cap ligand TPA [tris(2-pyridylmethyl)amine] coordinated to metal ions Fe(III), Co(II) or Mn(II) were used. The reactions with these compounds yielded four types of powder, P1, P2, P3 and P4. The physical and chemical analysis allowed to propose the composition of P1 as the trinuclear compound [{Fe(TPA)}2Cu(opba)]Cl4, as well [Fe2(-O)2(TPA)2]Cl2and Fe2O3 with the molar ratio 1:2/5:1/5. The experimental and calculated values of MT and MS obtained from the applied field or the temperature versus the magnetization curves were compared. These curves revealed the possibility that the Fe3+ ion has an intermediate state between low and high spin, which S = 3/2 to Fe3+ ion at room temperature with spin conversion to S = 1/2 towards the sample cooling.The MT x T curve shows that the sample presents an antiferromagneticintermolecular interaction below 14 K. The other powder compositions were estimated by the physical and chemical analysis to allow the proposed chemical formula. Therefore the formula corresponding to P2 and P3 are [{Co(TPA)}2{Cu(opba)}2CoCl2]·3H2O and [{Mn(TPA)}2{Cu(opba)}2MnCl2]·3H2O respectively, and that corresponding to P4 is [{Co(TPA)}2Cu{Cu(opba-dN)}2] and [CoCu(opba-dN)]n. This work also describes the study of the magnetic properties of the ferrihydrite obtained from the reaction between molecular nanomagnets precursors. Mössbauer and magnetization data show a narrow distribution of particle size with a mean diameter of 5,0 nm.